Extrusion-instabilities from non-linear rheology for industrial polyethylene - Cyriac, Febin (2013)
The instabilities that occur in the pressure-driven extrusion of molten polymers are fascinating from the scientific perspective but troublesome and sometimes catastrophic from the industrial one. Flow anomalies like sharkskin, Stick-Slip and Gross Melt fracture can occur in common extrusion operations such as the manufacture of polymeric rods, tubes, sheets, films, tanks or wire coating. Over the years, processors have learned to work around these processing defects by a variety of means: slowing the manufacturing rate, increasing the melt temperature or by- addition of processing additives. All these solutions can be proven extremely costly, thus a significant interest and effort is put in designing and manufacturing polymers with better processing-properties and lower potential to flow-instabilities. Sharkskin, here defined as periodic surface distortions of low amplitude and high frequency, is most commonly observed in polyethylene’s of sufficiently narrow molecular weight. One reason why sharkskin is of great importance is that as the extrusion flow rate increases, it is in many cases the first instability to occur, it is challenging to suppress and affects an important product quality parameter, namely the surface appearance. FT Rheology can be used to study different PE industrial samples with respect to their behavior under the LAOS flow. The resulting non-linearities showed a dependency on both the molecular weight and topology [1]. Filipe et al. [1] found out that for strain amplitudes above a critical value, the stress time signal exhibited an amplitude decay that indicates slip in qualitative agreement with Chen et al. [2] and Hatzikiriakos and Dealy [3]. The second harmonic was thus found to become significant (above noise level) at the onset of the stress amplitude decay and it is found to be a useful indicator of secondary flows or generally instabilities. [1]